Peran Kedudukan Parboru dan Hula-hula dalam Penyelesaian Sengketa Perceraian Adat Batak Toba - Kevin Andreas Halomoan Tambunan; Sri Hadiningrum; Parlaungan Gabriel Siahaan; Lusi Harianja; Novita Sarah Simanjuntak; Auliya Putri Risky (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study is entitled "The Role of Parboru and Hula-Hula in the Settlement of Divorce Disputes in Batak Toba Customs". The main focus of this study is to analyze the role and position of Parboru (the woman's family) and Hula-Hula (the wife's family) in the divorce settlement process according to Batak Toba customs. This study also presents the dynamics of the interaction of the two elements in customary mediation, as well as how customary values ​​and norms are implemented to maintain the harmony and dignity of the extended family. The method used in this study is a qualitative method with a descriptive approach. Data obtained through interviews and library studies of relevant literature on Batak Toba customary law, Dalihan Na Tolu, and the role of Parboru and Hula-Hula in traditional ceremonies and the resolution of marital conflicts in Batak Toba customs. The results of the study indicate that Hula-Hula has a central position as a decision maker and mediator, while Parboru plays a role as a technical implementer, mediator, and balancer in the customary deliberation forum. The active involvement of both parties is very important to ensure that the divorce process runs according to customary norms and maintains the social harmony of the Batak Toba community. This study is expected to enrich the literature on Batak customary law and become a reference for students, the community, and customary leaders in understanding the importance of the role of kinship in resolving divorce.